SANKSI HUKUM BAGI PENGURUS YANG MENGHALANGI PROSES PEMBERESAN KEKAYAAN YAYASAN YANG DIBUBARKAN BERDASARKAN PUTUSAN PENGADILAN (STUDI KASUS PEMBUBARAN YAYASAN BHAKTI SOSIAL SURAKARTA BERDASARKAN PUTUSAN MAHKAMAH AGUNG NOMOR 625 K/Pdt/2012) - Jeanet Trifena Lewi; Gunawan Djajaputra (Jurnal Hukum Adigama, 2018)
This study examines the fact that a foundation as a social institution can be dissolved by the causes as regulated by the Foundation Law, as happened to Yayasan Bhakti Sosial Surakarta which was dissolved by the decision of Surakarta District Court No. 141 / Pdt G / 2010 / PN Ska which has been upheld by the decision of the High Court of Semarang No. 233 / Pdt / 2011 / PT Smg and Supreme Court ruling Number 625 K / Pdt / 2012. Problems in this research is that there has been an act of disagreement by the Board of Bhakti Social Foundation of Surakarta against the liquidator in the socialization of the Bhakti Social Foundation of Surakarta. Based on the results of research and discussion it can be concluded that basically the nature of the decision dissolving the Bhakti Social Foundation based on the Supreme Court's decision Number 625 K / Pdt / 2012 is a declarative decision (declaratoir) a verdict that does not require any execution action. Law Number 16 Year 2001 jo. Law Number 28 Year 2004 About the Foundation does not clearly regulate the confiscation of the Foundation's wealth including sanctions to the board of the Foundation that take action against the work of the liquidator.